A clinical and molecular epidemiological survey of hepatitis C in Blantyre, Malawi, suggests a historic mechanism of transmission. Issue 4 (9th February 2022) - Stockdale, Alexander J.; Kreuels, Benno; Shawa, Isaac T.; Meiring, James E.; Thindwa, Deus; Silungwe, Niza M.; Chetcuti, Karen; Joekes, Elizabeth; Mbewe, Maurice; Mbale, Blessings; Patel, Pratiksha; Kachala, Rabson; et al.
Abstract: Hepatitis C virus (HCV) is a leading cause of liver disease worldwide. There are no previous representative community HCV prevalence studies from Southern Africa, and limited genotypic data. Epidemiological data are required to inform an effective public health response. We conducted a household census‐based random sampling serological survey, and a prospective hospital‐based study of patients with cirrhosis and hepatocellular carcinoma (HCC) in Blantyre, Malawi. We tested participants with an HCV antigen/antibody ELISA (Monolisa, Bio‐Rad), confirmed with PCR (GeneXpert, Cepheid) and used line immunoassay (Inno‐LIA, Fujiribio) for RNA‐negative participants. We did target‐enrichment whole‐genome HCV sequencing (NextSeq, Illumina). Among 96, 386 censused individuals, we randomly selected 1661 people aged ≥16 years. Population‐standardized HCV RNA prevalence was 0.2% (95% CI 0.1–0.5). Among 236 patients with cirrhosis and HCC, HCV RNA prevalence was 1.9% and 5.0%, respectively. Mapping showed that HCV RNA+ patients were from peri‐urban areas surrounding Blantyre. Community and hospital HCV RNA+ participants were older than comparator HCV RNA‐negative populations (median 53 vs 30 years for community, p = 0.01 and 68 vs 40 years for cirrhosis/HCC, p < 0.001). Endemic HCV genotypes ( n = 10) were 4v (50%), 4r (30%) and 4w (10%). In this first census‐based community serological study in Southern Africa, HCV was uncommon in the general population, was centred on peri‐urban regions and was attributable for <5% of liver disease. HCV infection was observed only among older people, suggesting a historic mechanism of transmission. Genotype 4r, which has been associated with treatment failure with ledipasvir and daclatasvir, is endemic.